Gender and the impact of COVID-19 on demand for and access to health care: analysis of data from Kenya, Nigeria, and South Africa - Abdalla, Safa; Katz, Elizabeth G; Darmstadt, Gary L (The Lancet global health, 2021)
Global health emergencies can impact men and women differently due to gender norms that affect exposures and care-seeking. Likewise, economic and social upheaval can affect men and women unequally. These effects may be unfolding with the current COVID-19 pandemic given women's economic vulnerability and disproportionate caregiving burden. Global data have shown a decline in access to health care that was more pronounced among women. Here, we aim to investigate gender differences in the impact of COVID-19 by looking at intersectionality of gender with educational and socioeconomic factors in Kenya, Nigeria, and South Africa. Data were collected by Opinion Research Business International using representative sampling with census data as the sampling frame. Around 1000 participants from each country were interviewed by telephone. Participants reported their retrospective experiences with health care in the period between December, 2019, and February, 2020, before the pandemic, and in the time period between March and July, 2020, during the pandemic. We used conditional logistic regression, with the respondent as their own control, to estimate the change in access to health care after the pandemic's onset among men and women, stratified by educational level (none, primary or secondary education, and post-secondary education). We also examined the change in demand for preventive care and care for non-communicable conditions, stratified by the respondent's self-reported experience of financial difficulty due to the pandemic. Among those who reported a need to seek health care during both time periods in South Africa, a decline in the ability to see a health-care provider since March 2020 was greater for women than for men, a gap that was more evident in the group that did not have post-secondary education (OR=0·08, p=0·04 for women; no change for men) than for those with post-secondary education (0·2, p=0·24 for women; 0·5, p =0·69 for men). South African women who were financially affected were more likely than men to seek preventive care initially (6% vs 2%, respectively), and had a significant decline in seeking preventive care since March 2020 (0·23, p=0·04). The reduction in men was not statistically significant (0·67, p=0·57). No such effects were noted in Nigeria or Kenya. In South Africa, the detrimental effect of COVID-19 on health-care access seemed more pronounced for women who did not have post-secondary education than for men in the same group, and also compared with men and women with post-secondary education. Women may be deprioritising preventive and routine care after financial difficulties caused by COVID-19 and its control measures. Bill and Melinda Gates Foundation.